Perceived roles of community doctors in protecting children with disabilities against maltreatment in low-resource communities in the Philippines - Paolo Diaz Mangune (Child Protection and Practice)
Background: Given the distinct and evolving needs of children with disabilities, doctors-to-the-barrios, community doctors deployed in low-resource areas in the Philippines, may be regarded to be in an ideal position to provide protective services for these children. Objective: To explore the perspectives of community doctors about their perceived roles in employing protective mechanisms for children with disabilities. Participants and setting: Twelve community doctors deployed in three major island groups in the Philippines participated in this study. Method: This study used a qualitative research approach, anchored on the methodological and ethical commitments of Sikolohiyang Pilipino. The participants agreed to take part in an online pakikipagkwentuhan (akin to semi-structured interview). The audio file recordings from these interviews were transcribed. These transcripts were subjected to inductive thematic analysis. Results: Five main themes were identified about the perceived roles of community doctors in employing protective mechanisms for children with disabilities. These include: (a) identifying and monitoring children with disabilities, (b) attending to the health-related needs of the family, (c) detecting red flags for suspected cases of abuse, (d) providing medical intervention to incidents of abuse, and (e) ensuring the continuity of legal proceedings. Conclusion: The themes in the study affirm that community doctors occupy a unique space in employing a spectrum of protective measures for children with disabilities as they are among the few, if not the only one, providing crucial health-related services to this group of children, their families, and their communities.